2009
DOI: 10.1002/anie.200902861
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoelectrochemical Study of Vertically Aligned Silicon Nanowire Arrays

Abstract: Wiring photoelectrodes: Vertically aligned silicon nanowires were chemically synthesized and tested for solar‐energy harnessing. Growth experiments reveal that such nanowire arrays can be obtained when the growth is slow. Photoelectrochemical studies validate that silicon nanowires are promising candidates for efficient solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…Si nanowires (SiNWs) have been considered as novel class of nanostructured materials for highperformance devices [3,4] due to their unique structural, electrical, optical, and thermoelectric properties. Recently, SiNWs have been widely investigation for developing next-generation solar cells to realize both low cost and high efficiency [5][6][7][8][9]. SiNWs can be prepared by two main methods including bottom-up and top-down fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Si nanowires (SiNWs) have been considered as novel class of nanostructured materials for highperformance devices [3,4] due to their unique structural, electrical, optical, and thermoelectric properties. Recently, SiNWs have been widely investigation for developing next-generation solar cells to realize both low cost and high efficiency [5][6][7][8][9]. SiNWs can be prepared by two main methods including bottom-up and top-down fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…After the deposition of a platinum catalyst on the electroless etched Si nanowires, Peng et al (2009) reported an apparent energy conversion efficiency of up to 8.14 % in Br -/Br 2 electrolyte. Following a similar synthesis method, Yuan et al (2009) reported an efficiency of 10.1 % in 1 M LiClO 4 with Me 2 Fc +/0 redox pair under 100 mW/cm 2 of illumination. Dai et al (2013) used atomic layer deposition (ALD) to deposit Pt nanoparticles, as HER catalyst, on Si nanowires prepared using electroless etching, which gave better turn-on voltages than planar silicon ( Fig.…”
Section: Solution Phase Methodsmentioning
confidence: 99%
“…After the temperature reaches the Au-Si eutectic point, Au-Si alloy droplets will form, which then adsorbs the Si precursor, resulting in nucleation. Yuan et al (2009) synthesized n-type Si nanowire in CVD system by a slow Si precursor feeding rate to achieve a slow growth rate. Efficient energy conversion was achieved using the highly oriented Si nanowires, with 20 μm length and 200 nm width, in a Me 2 Fc/ Me 2 Fc + electrolyte.…”
Section: Gas Phase Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one-dimensional (1D) nanostructures provide a promising and prospective approach to fabricate low-cost and high-performance optoelectronic devices owning to their large length-to-diameter and surface-to-volume ratios. [3][4][5][6] First, excellent light absorption can be realized from 1D nanostructure arrays with a small volume due to their moth-eye-like morphology perfect for antireflection effect 7,8 and light confinement under various optical mechanisms. [9][10][11] Second, the promising orthogonal spatial relation between carrier separation and photon absorption (via radial junction) guarantees a short diffusion distance and an effective carrier collection, allowing the lowgrade materials to be available for high-performance optoelectronic devices.…”
mentioning
confidence: 99%